PENGARUH PENGEMBANGAN KARIR DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP RETENSI KARYAWAN MELALUI KEPUASAN KERJA PADA BANK MANDIRI TASPEN KCP BOJONEGORO DAN LAMONGAN - Cipto; Woro Utari; Nugroho Mardi Wibowo (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This study aims to describe career development, perceived organizational support, employee retention, and job satisfaction of employees at Bank Mandiri Taspen KCP Bojonegoro and Lamongan, and to analyze the direct and indirect effects of career development and perceived organizational support on employee retention through job satisfaction. This explanatory research employs a quantitative approach, using census sampling for the entire population of 31 employees, with data analyzed using Partial Least Square (PLS). The results show that retention, career development, and organizational support are categorized as very high, while job satisfaction is categorized as high. Career development does not have a significant direct effect on job satisfaction, but perceived organizational support does have a significant direct effect. Directly, job satisfaction, career development, and organizational support significantly affect employee retention. Indirectly, career development does not significantly affect employee retention through job satisfaction, while perceived organizational support does have a significant effect on employee retention through job satisfaction.